2020
DOI: 10.1007/s40618-020-01460-w
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone concentrations in severely or critically ill patients with COVID-19

Abstract: Objective COVID-19 is a new coronavirus infectious disease. We aimed to study the characteristics of thyroid hormone levels in patients with COVID-19 and to explore whether thyroid hormone predicts all-cause mortality of severely or critically ill patients. Methods The clinical data of 100 patients with COVID-19, who were admitted to Wuhan Tongji Hospital from February 8 to March 8, 2020, were analyzed in this retrospective study. The patients were followed up for 6–41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
95
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 28 publications
15
95
1
Order By: Relevance
“…This correlation was confirmed by further studies [84,85], in particular Gao et al grouped 100 patients into non-severely ill patients, survivors and non-survivors displaying mean FT3 values of 4.40, 3.73 and 2.76 pmol/L, respectively. Hence, FT3 levels were significantly lower in patients with severe COVID-19 disease and FT3 levels lower than 3.10 pmol/L predicted morality independently from all other causes [84]. Moreover, a study was performed in 40 COVID-19 patients with non-severe symptoms, matched to 54 healthy subjects by age and gender; serum samples were collected at 1st, 4th, 7th and 10th day of hospitalization and, compared to controls.…”
Section: Sars-cov-2 and Thyroidmentioning
confidence: 62%
See 1 more Smart Citation
“…This correlation was confirmed by further studies [84,85], in particular Gao et al grouped 100 patients into non-severely ill patients, survivors and non-survivors displaying mean FT3 values of 4.40, 3.73 and 2.76 pmol/L, respectively. Hence, FT3 levels were significantly lower in patients with severe COVID-19 disease and FT3 levels lower than 3.10 pmol/L predicted morality independently from all other causes [84]. Moreover, a study was performed in 40 COVID-19 patients with non-severe symptoms, matched to 54 healthy subjects by age and gender; serum samples were collected at 1st, 4th, 7th and 10th day of hospitalization and, compared to controls.…”
Section: Sars-cov-2 and Thyroidmentioning
confidence: 62%
“…In all these patients, mortality correlated with the severity of thyroid hormone changes, while pre-existent thyroid diseases were not recorded [83]. This correlation was confirmed by further studies [84,85], in particular Gao et al grouped 100 patients into non-severely ill patients, survivors and non-survivors displaying mean FT3 values of 4.40, 3.73 and 2.76 pmol/L, respectively. Hence, FT3 levels were significantly lower in patients with severe COVID-19 disease and FT3 levels lower than 3.10 pmol/L predicted morality independently from all other causes [84].…”
Section: Sars-cov-2 and Thyroidmentioning
confidence: 66%
“…In further study by Gao et al [ 116 ], thyroid function parameters were evaluated in a cohort of 100 COVID-19 patients from Wuhan, and findings were compared between critical and non-critical patients. Results showed that TSH and FT3 levels, but not FT4 levels, were significantly lower in critically ill patients when compared with the non-critically ill ones.…”
Section: Thyroid Function Alterations In Patients With Covid-19 Diseamentioning
confidence: 99%
“…Among these records, 141 were excluded (114 because outside the field of interest, 13 as reviews/editorials/letters, 14 as case reports or small case series). Eight original articles were selected and retrieved in full-text version [6][7][8][9][10][11][12][13]. One article was excluded after reading the full text [6].…”
Section: Literature Searchmentioning
confidence: 99%